Pemanfaatan Daerah Aliran Sungai Sedudut Sebagai Rintisan Eduwisata di RT 03 RW 06 Mulyorejo Kota Malang - Afdah, Umi; Sulistyo, Mikael Adri Budi; Rahayu, Yekti Sri; Rahmawati, Mariana Fitri (Universitas Tribhuwana Tunggadewi Malang, 2023)
The Sedudut river basin across RT 3 RW 6 Mulyorejo Subdistrict is still not managed well, causing problems such as silting of the river, uneven water flow, environmental pollution, accumulation of rubbish, unpleasant odors and lots of mosquitoes. The aim of community service is to raise awareness among residents and farmer cadets to manage river watersheds to become educational tourism pilots. The method used is community education and advocacy to local governments to create educational tourism targeting residents and farming cadets. The results have been the realization of pioneering educational tourism and institutional strengthening of Sariwongso farmer cadets in managing river watersheds. Support from RT administrators and community leaders increases the involvement of Taruna Tani Sariwangso in managing the Sedudut river basin. The benefits felt by local residents include: the flow of river water is smooth, so there are no piles of rubbish which cause odors and the growth of mosquitoes. The wareng system that has been built has increased from 3 to 5 warengs so that the management of river cleanliness by the residents of RT 3 RW 6 is getting better. The young group of Taruna Tani has been actively pioneering activities in RW6, strengthened by the issuance of the Decree on the Establishment of Taruna Tani which has been ratified by the local RT Head. The number of residents involved previously increased from 4 people to 16 people. The Malang City Government provides support for facilities (fish seeds, feed, harvest nets) and pedestrian infrastructure and fenced bridges to support educational tourism pilots for management of the Sedudut river area.ABSTRAKDaerah aliran sungai Sedudut melintasi RT 3 RW 6 Kelurahan Mulyorejo masih belum dikelola dengan baik sehingga menimbulkan permasalahan seperti pendangkalan sungai, aliran air tidak lancar, pencemaran lingkungan, penumpukan sampah, berbau tidak sedap dan banyak nyamuk. Tujuan pengabdian masyarakat untuk menumbuhkan kesadaran warga dan taruna tani untuk mengelola daerah aliran sungai untuk dijadikan rintisan wisata edukasi. Metode yang digunakan adalah pendidikan masyarakat dan advokasi kepada pemerintah daerah untuk mewujudkan wisata edukasi dengan sasaran warga dan taruna tani. Hasilnya telah terwujud rintisan wisata edukasi dan penguatan kelembagaan taruna tani Sariwongso dalam mengelola daerah aliran sungai. Dukungan pengurus RT dan tokoh masyarakat menumbuhkan keterlibatan Taruna Tani Sariwangso untuk mengelola daerah aliran sungai Sedudut. Manfaat yang dirasakan warga sekitar, seperti: aliran air sungai lancar, sehingga tidak terjadi tumpukan sampah yang menyebabkan bau dan perkembangan nyamuk. Sistem wareng yang terbangun bertambah dari 3 menjadi 5 wareng sehingga pengelolaan kebersihan sungai oleh warga RT 3 RW 6 semakin baik. Kelompok muda Taruna Tani telah aktif merintis kegiatan di RW6 diperkuat dengan terbitnya SK Pendirian Taruna Tani yang telah disahkan Ketua RT setempat. Jumlah warga yang terlibat sebelumnya 4 orang menjadi 16 orang. Pemerintah Kota Malang memberikan dukungan sarana (benih ikan, pakan, alat jaring panen) dan prasarana pedesterian dan jembatan berpagar untuk mendukung rintisan wisata edukasi pengelolaan daerah sungai Sedudut.